Analysis of the Auditory Feedback and Phonation in Normal Voices - Arbeiter, Mareike; Petermann, Simon; Hoppe, Ulrich; Bohr, Christopher; Döllinger, Michael; Ziethe, Anke (Annals of Otology Rhinology and Laryngology, 2018)
PURPOSE: The aim of this study was to investigate the auditory feedback mechanisms and voice quality during phonation in response to a spontaneous pitch change in the auditory feedback. Does the pitch shift reflex (PSR) change voice pitch and voice quality? Quantitative and qualitative voice characteristics were analyzed during the PSR. METHOD: Twenty-eight healthy subjects underwent transnasal high-speed video endoscopy (HSV) at 8000 fps during sustained phonation [a]. While phonating, the subjects heard their sound pitched up for 700 cents (interval of a fifth), lasting 300 milliseconds in their auditory feedback. The electroencephalography (EEG), acoustic voice signal, electroglottography (EGG), and high-speed-videoendoscopy (HSV) were analyzed to compare feedback mechanisms for the pitched and unpitched condition of the phonation paradigm statistically. Furthermore, quantitative and qualitative voice characteristics were analyzed. RESULTS: The PSR was successfully detected within all signals of the experimental tools (EEG, EGG, acoustic voice signal, HSV). A significant increase of the perturbation measures and an increase of the values of the acoustic parameters during the PSR were observed, especially for the audio signal. CONCLUSIONS: The auditory feedback mechanism seems not only to control for voice pitch but also for voice quality aspects.
EVALuna2:33156